Предмет: Математика,
автор: RoDggeR
sin(α-3π/2)cos(2π-α)-sin(π-α)sin(π+α)
Ответы
Автор ответа:
0
sin(a-3pi/2) = cosa
cos(2pi-a) = cosa
sin(pi-a) = sina
sin(pi+a) = -sina
В итоге получаем
cos^2a+sin^2a = 1 ( основное тригонометрическое тождество )
cos(2pi-a) = cosa
sin(pi-a) = sina
sin(pi+a) = -sina
В итоге получаем
cos^2a+sin^2a = 1 ( основное тригонометрическое тождество )
Автор ответа:
0
sin(a-3π/2)*cos(2π-a)-sin(π-a)*sin(π+a)=
=-sin(3π/2-a)*cosa-sina*(-sina)=-(-cosa)*cosa+sin²a=
=cos²a+sin²a=1
=-sin(3π/2-a)*cosa-sina*(-sina)=-(-cosa)*cosa+sin²a=
=cos²a+sin²a=1
Похожие вопросы
Предмет: Қазақ тiлi,
автор: nurgulsarbaeva62
Предмет: Английский язык,
автор: Lalaahmedbeyli39
Предмет: Музыка,
автор: igrakles33
Предмет: Химия,
автор: lizavetka1407